Effects of Cuscuton dynamics on braneworld configurations in the scalar–tensor representation of $$f\left( R,T\right) $$ f R , T gravity - João Luís Rosa; D. Bazeia; A. S. Lobão (European Physical Journal C: Particles and Fields, 2022)
Abstract In this work we study braneworld configurations in the scalar–tensor representation of the $$f\left( R,T\right) $$ f R , T gravity theory in the presence of a Cuscuton term in the source field matter Lagrangian. We start by deriving the scalar–tensor representation of the theory and obtaining its respective equations of motion. We then introduce the standard metric for a flat braneworld model with one extra dimension for the general case of a $$f\left( R,T\right) $$ f R , T theory and study two different models for the source field. Given the complexity of the field equations, these solutions are obtained numerically. In these cases, the Cuscuton term effectively amplifies the effect, by increasing the height of the stability potential barrier and, consequently, the depth of the minimum of the graviton zero-mode on the brane. Finally, we study the particular cases of $$F(R)+T$$ F ( R ) + T and $$R+G\left( T\right) $$ R + G T , for which only the scalar fields $$φ $$ φ or $$ψ $$ ψ are present, respectively, and we prove that the presence of the scalar field $$φ $$ φ is essential in the development of internal structure on the brane.